Assessment of extraction options for a next‐generation biofuel: Recovery of bio‐isobutanol from aqueous solutions. Issue 10 (18th June 2021) - Fu, Chuhan; Li, Zhuoxi; Zhang, Yulei; Yi, Conghua; Xie, Shaoqu
Abstract: Isobutanol is a widely used platform compound and a raw material for synthesizing many high value‐added compounds. It also has excellent fuel properties and is an ideal gasoline additive or substitute with a very broad development space. Isobutanol production by biological fermentation has the advantages of a comprehensive source of raw materials, low cost, environmental protection, and sustainability. However, it also has disadvantages such as many impurities, low isobutanol concentration, and difficulty separating the water + isobutanol azeotrope. Thus, it is necessary to explore an appropriate downstream separation process for the water + isobutanol azeotrope. K2 CO3 with a strong salting‐out effect was used as the salting‐out agent, and the salting‐out of isobutanol from aqueous solutions was investigated at 298.15 K. The effect of the initial salt concentration in the aqueous solution, the recovery of isobutanol, and the effect of dehydration were investigated in detail. The e‐NRTL‐RK model was employed to generate the binary parameters for isobutanol and water, and electrolyte pair parameters for water/isobutanol and ions to reproduce the phase diagram with high accuracy. The processes of solvent extractive distillation, and salting‐out + distillation were simulated by Aspen Plus. The energy consumptions for the solvent‐based and salting‐out‐based processes were compared. The salting‐out + distillation process turned out to be more energy‐saving than the solvent extraction process.